PELATIHAN TENTANG SUPLEMENTASI RASIONAL OLEH BIDAN PADA IBU HAMIL DAN EDUKASI MENGGUNAKAN MEDIA SOSIAL INSTAGRAM - Bernadette Dian Novita; Sianty Dewi; Evelyn Ongkodjojo; Maria Yuliastuti (LPPM, Universitas Katolik Widya Mandala Surabaya, 2022)
Rational drugs use is a must know-knowledge in preventing disability and death due to unnecessary drug use. Giving supplementation during pregnancy aims to reduce infant mortality and disability. Refreshing the rational use of supplementation in pregnancy and sharing knowledge in how to use Instagram as an education and communication media between midwives and pregnant women aims in improving the midwives’ skills as educators and good communicators. The method of this activity was divided into three stages, preparation, implementation, and evaluation. In the implementation stage, midwives’ knowledge about supplementation rational and social media use were increasing. the evaluation stage showed that the midwives could use Instagram as education and communication media between midwives and pregnant women